PERLINDUNGAN HUKUM TERHADAP SAKSI DAN KORBAN KEJAHATAN DALAM PROSES PERADILAN PIDANA DI INDONESIA - Rini Retno Winarni (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2011)
There are many articles of KUHAP (Criminal Law of Procedure) which regulates the protection of criminal causes less for the protection of victim actually, the equal protection for witness (victim) as the adagium said